The green piano how little me found music - Flack, Roberta 1937-2025; Bolden, Tonya 1959- (Anne Schwartz Books, 2023)
This autobiographical picture book by the multiple Grammy Award-winning singer Roberta Flack recounts her childhood in a home surrounded by music and love: it all started with a beat-up piano that her father found in a junkyard, repaired, and painted green. Growing up in a Blue Ridge mountain town, little Roberta didn't have fancy clothes or expensive toys...but she did have music. And she dreamed of having her own piano. When her daddy spies an old, beat-up upright piano in a junkyard, he knows he can make his daughter's dream come true. He brings it home, cleans and tunes it, and paints it a grassy green. And soon the little girl has an instrument to practice on, and a new dream to reach for--one that will make her become a legend in the music industry. Here is a lyrical picture book--perfect for aspiring piano players and singers--that shares an intimate look at Roberta Flack's family and her special connection to music.
Keywords: Flack, Roberta -- 1937-2025; Musik; Kind; Enthusiasmus; Klavier; Familie; Flack, Roberta / Childhood and youth / Juvenile literature; African American women singers / Biography / Juvenile literature; Chanteuses noires américaines / Biographies / Ouvrages pour la jeunesse; JUVENILE NONFICTION / Biography & Autobiography / Music; JUVENILE NONFICTION / Music / Popular; JUVENILE NONFICTION / People & Places / United States / African American & Black; Flack, Roberta; Childhood and youth of a person; African American women singers; Gender identity / Juvenile literature; Picture books for children; autobiographies (literary works); picture books; Creative nonfiction; Picture books; Autobiographies; Biographies; Juvenile works; Livres d'images; Essais fictionnels; Bilderbuch; Autobiografie